2016
DOI: 10.1152/japplphysiol.00473.2016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of respiratory output by cervical epidural stimulation in the anesthetized mouse

Abstract: Respiration is produced and controlled by well-characterized brain stem nuclei, but the contributions of spinal circuits to respiratory control and modulation remain under investigation. Many respiratory studies are conducted in in vitro preparations (e.g., brain stem slice) obtained from neonatal rodents. While informative, these studies do not fully recapitulate the complex afferent and efferent neural circuits that are likely to be involved in eupnea (i.e., quiet breathing). To begin to investigate spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…We have further demonstrated in this study that high-density spinal cord arrays are able to produce completely different recruitment patterns within the same spinal level simply by changing the active electrode within the array. This result suggests that high-density electrode arrays could be particularly beneficial to optimize SCS for improving bladder function-or any other function of interest at other spinal levels [40][41][42][43][44][45] -and that existing commercial stimulation leads may be inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…We have further demonstrated in this study that high-density spinal cord arrays are able to produce completely different recruitment patterns within the same spinal level simply by changing the active electrode within the array. This result suggests that high-density electrode arrays could be particularly beneficial to optimize SCS for improving bladder function-or any other function of interest at other spinal levels [40][41][42][43][44][45] -and that existing commercial stimulation leads may be inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…The surgically accessible locations targeted for epidural stimulation comprised eight dorsal locations of the cervical spinal cord corresponding to each spinal level in addition to the site between C3 and C4 (C3/4). We identified C3/4 as a potential target for modulating respiration in our previous study of mice (Huang et al, 2016) (Fig. 1A).…”
Section: Experimental Protocolmentioning
confidence: 94%
“…Finally, future experiments aiming to identify spinal PMN excitatory burst populations in more anatomical detail could lead to a diaphragm “pacing” device (Huang et al, 2016; Kowalski et al, 2013). We demonstrate pacing of spinal cord derived PMN bursting at a rate similar to fictive inspiration, and given considerable technical advancements, this proof-of-concept could be therapeutically relevant in vivo after cervical spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is also data indicating that in the absence of supraspinal (rVRG) input, PMN activity can be initiated centrally by various pharmacological manipulations (Coglianese et al, 1977; Ghali and Marchenko, 2016; Reinoso et al, 1996; Viala et al, 1979; Zimmer and Goshgarian, 2007), or by electrical stimulation (Huang et al, 2016; Kowalski et al, 2013). Although it has been suggested that this activity might be generated by a spinal analogue of the preBötC (Ghali and Marchenko, 2016), the origin of this activity has always been elusive.…”
Section: Introductionmentioning
confidence: 99%